2017
DOI: 10.1016/j.jcmgh.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Esophageal Submucosal Gland Culture Model Shows Capacity for Proliferation and Differentiation

Abstract: Background & AimsAlthough cells comprising esophageal submucosal glands (ESMGs) represent a potential progenitor cell niche, new models are needed to understand their capacity to proliferate and differentiate. By histologic appearance, ESMGs have been associated with both overlying normal squamous epithelium and columnar epithelium. Our aim was to assess ESMG proliferation and differentiation in a 3-dimensional culture model.MethodsWe evaluated proliferation in human ESMGs from normal and diseased tissue by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…in gene or protein expression and cellular appearance) between BO and selected normal tissues - including the intestine, gastric pylorus, gastric corpus and gastric cardia – have found some shared attributes 11 , 12 . There is also evidence suggesting BO may originate directly from native oesophageal squamous 13 or submucosal gland cells 14 17 , from recruitment of circulating stem cells 18 , or from reactivation of dormant p63 − /KRT7 + residual embryonic cells (RECs) in situ 19 . In contrast to p63 − /KRT7 + RECs, a recent study identified p63 + /KRT5 + /KRT7 + cells derived from the squamocolumnar junction as the cells of origin of BO in a transgenic mouse model with ectopic expression of CDX2 in KRT5 + epithelium 20 .…”
Section: Introductionmentioning
confidence: 99%
“…in gene or protein expression and cellular appearance) between BO and selected normal tissues - including the intestine, gastric pylorus, gastric corpus and gastric cardia – have found some shared attributes 11 , 12 . There is also evidence suggesting BO may originate directly from native oesophageal squamous 13 or submucosal gland cells 14 17 , from recruitment of circulating stem cells 18 , or from reactivation of dormant p63 − /KRT7 + residual embryonic cells (RECs) in situ 19 . In contrast to p63 − /KRT7 + RECs, a recent study identified p63 + /KRT5 + /KRT7 + cells derived from the squamocolumnar junction as the cells of origin of BO in a transgenic mouse model with ectopic expression of CDX2 in KRT5 + epithelium 20 .…”
Section: Introductionmentioning
confidence: 99%
“…64 Porcine ESMGs placed in 3-dimensional culture also proliferated and single cells derived from these ESMGs formed 2 types of spheroids, which recapitulated the squamous and columnar phenotypes associated with ESMGs in the human and dog studies. 65 One spheroid type had a solid, squamous appearance and expressed squamous markers, such as p63, whereas the other was hollow and expressed columnar cell markers found in Barrett's metaplasia, including AGR2, MUC13, KRT18, MUC1, KRT8, and SOX9. Research is underway in pigs to elucidate factors that affect expression of squamous vs columnar markers.…”
Section: August 2019mentioning
confidence: 95%
“…Jiang et al 142 identified unique p63-positive transitional basal cells expressing cytokeratins K5 and K7 as a putative BE cell of origin along with functional validation in 3D organoid assays. In addition, von Furstenberg et al 143 used a porcine model of epithelial injury and human tissues to identify 2 distinct esophageal submucosal gland–derived cells expressing p63 or K7 that give rise to squamous and ductal 3D spheroid structures, respectively.…”
Section: Modeling Neoplastic and Preneoplastic Conditions In 3dmentioning
confidence: 99%